Plasma Phospholipid Fatty Acid Profile is Altered in Both Septic and Non-Septic Critically Ill: A Correlation with Inflammatory Markers and Albumin - Novak, František; Borovska, J; Vecka, M; Rychlikova, J; Vavrova, L; Petraskova, H; Zak, A; Novakova, O (Lipids, 2017)
This study analyzes fatty acid (FA) composition in plasma lipids and erythrocyte phospholipids while comparing septic and non-septic critically ill patients. The aim was to describe impacts of infection and the inflammatory process. Patients with severe sepsis (SP, n = 13); age-, sex- and APACHE II score-matched non-septic critically ill with systemic inflammatory response syndrome (NSP, n = 13); and age-/sex-matched healthy controls (HC, n = 13) were included in a prospective case-control study during the first 24 h after admission to the intensive care unit. In both SP and NSP, lower n-6 polyunsaturated FA (PUFA) accompanied by higher proportions of monounsaturated FA (MUFA) in plasma phospholipids (PPL) was observed relative to HC. MUFA proportion was negatively correlated with n-6 PUFA, high density lipoprotein cholesterol (HDL-C), and albumin. MUFA was positively correlated with C-reactive protein (CRP), procalcitonin (PCT), interleukins (IL-6, IL-10), oxidized low density lipoproteins (ox-LDL), and conjugated dienes (CD). In both SP and NSP, inflammatory and lipid peroxidation markers were significantly higher-CRP (p < 0.001; p = 0.08), IL-6, IL-10, TNF-α (p < 0.01, p = 0.06), ox-LDL, and CD while total cholesterol, HDL-C, LDL-C albumin, and 20:4n-6/22:6n-3 and n-6/n-3 ratios were lower compared to HC. In conclusion, the changes in plasma lipid FA profile relate to the intensity of inflammatory and peroxidative response regardless of insult etiology. The lower MUFA and higher n-6 PUFA proportions in PPL were inversely correlated with cholesterol and albumin levels.
Keywords: senioři; Fatty acid profile; C-Reactive Protein; kyseliny mastné mononenasycené; Sepsis; Inflammation; Male; Lipoproteins; C-reaktivní protein; Plasma lipids; Middle Aged; Fatty Acids; interleukiny; mužské pohlaví; studie případů a kontrol; Prospective Studies; Calcitonin; Interleukins; PUFA; ženské pohlaví; Humans; prospektivní studie; Phospholipids; kritický stav; biologické markery; Oxidative stress; Fatty Acids, Monounsaturated; sepse; lidé středního věku; kalcitonin; mastné kyseliny; Biomarkers; syndrom systémové zánětlivé reakce; Systemic Inflammatory Response Syndrome; Female; fosfolipidy; Aged; Critical Illness; lidé; Case-Control Studies